1988
DOI: 10.1159/000184895
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Urea Generation and Muscle Protein Degradation by Adrenalectomy in Acutely Uremic Rats

Abstract: The effect of adrenalectomy on the enhanced protein degradation in acute uremia was investigated. Therefore, serum urea nitrogen, urea N appearance and Nt-methylhistidine were followed in bilaterally nephrectomized rats. At 48 h after induction of uremia the animals displayed serum urea nitrogen levels of 223 ± 9.5 mg/dl as compared to 26.0 ± 1.0 mg/dl in sham-treated rats. This increment was significantly attenuated in acutely uremic, adrenalectomized animals (176 ± 6.0 mg/dl). When these rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Studies in our laboratory have provided support to this notion. Following adrenalectomy, we observed reduced rates of urea nitrogen (urea-N) appear ance and a decrease of muscle protein breakdown in acutely uremic rats [16]. However, investigations em ploying adrenalectomy as a model of glucocorticoid defi ciency are always burdened by the fact that concomi tantly a considerable source of catecholamines is re moved from the organism.…”
Section: Introductionmentioning
confidence: 92%
“…Studies in our laboratory have provided support to this notion. Following adrenalectomy, we observed reduced rates of urea nitrogen (urea-N) appear ance and a decrease of muscle protein breakdown in acutely uremic rats [16]. However, investigations em ploying adrenalectomy as a model of glucocorticoid defi ciency are always burdened by the fact that concomi tantly a considerable source of catecholamines is re moved from the organism.…”
Section: Introductionmentioning
confidence: 92%
“…Serum levels of BUN and creatinine and superoxide scavenging activity were used as indicators of renal protection. As one might suspect, an increase in the serum BUN level may also be induced by muscle protein breakdown [10,21], but muscle protein breakdown could not lead to an increase in the creatinine level [15]. As many authors have reported that an increase in both serum BUN and creatinine levels could be used clinically to imply renal insufficiency [5,20], we decided to choose the tests of serum BUN and creatinine levels as the indication of renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…After indomethacin application these parameters were within the same range in both BN groups as compared to sham animals. Furthermore, the UNA, which indicates protein degradation and provides us with information on the amount of amino acid release from skeletal muscle [3,9,16], was calculated for 48 h. The UNA significantly increased in both BN groups as compared to sham animals but did not change significantly with indomethacin treatment. The amino acid N~-MH has been found to be a parameter of myofibrillar breakdown since it is present solely within actin and myosin, and once it is released from skeletal muscle it cannot be reutilized [4,6,18].…”
Section: Discussionmentioning
confidence: 99%
“…As an indicator of protein degradation the urea nitrogen appearance (UNA) for 48 h was calculated [3,9]. Furthermore N~-methylhistidine (N~-MH) serum concentration was assayed [4,16] to estimate myofibrillar breakdown and also routine laboratory parameters (serum urea nitrogen, SUN; creatinine, potassium) were followed.…”
Section: Introductionmentioning
confidence: 99%